Penerapan Pembelajaran STEAM Berbasis Media Labirin untuk Meningkatkan Kreativitas Siswa dalam Pembelajaran IPA di Kelas VIII SMP - Jubelina Lawa Paretta; Nancy Susianna; Nerru Pranuta Murnaka (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2026)
Twenty-first-century science education requires creativity through active, contextual, and problem-solving-oriented learning experiences; however, science learning at the junior high school level requires strategies that connect conceptual mastery with students’ abilities to generate ideas, select alternatives, design solutions, and develop products. This study aims to analyze the implementation of Science, Technology, Engineering, Arts, and Mathematics (STEAM) learning using Labyrinth media and the improvement of students’ creativity through a pre-experimental One Group Pretest–Posttest design involving 20 students. Data were collected using a creativity rubric covering fluency, flexibility, originality, and elaboration, and were analyzed using the Shapiro–Wilk test, Paired Sample t-Test, and N-Gain analysis. The results showed an improvement in creativity after the intervention, with the Paired Sample t-Test producing a significance value of <0.05 and the N-Gain indicating a moderate level of improvement, demonstrating that the integration of STEAM and Labyrinth media encouraged students to observe problems, generate ideas, try strategies, design solutions, and actively evaluate outcomes. The novelty of this study lies in utilizing the Labyrinth as a platform for STEAM activities incorporating problems, choices, pathways, collaboration, and creative activities, thereby offering an innovative learning design for developing junior high school students’ creativity.